A review of Schiodtella formosana, with some remarks on the genus Schiodtella and description of a Japanese new species (Hemiptera: Heteroptera: Cydnidae) - Imura, Jimpei; Ishikawa, Tadashi (Zootaxa, 2009)
Schiodtella formosana (= Stibaropus formosanus) in Taiwan and Japan is studied taxonomically. Taiwanese specimens are identified as ‘true’ Sc. formosana, whereas Japanese specimens represent a new species described herein as Sc. japonica sp. nov. This new species shows obvious variation in the hemelytra and tarsi, and can be distinguished from Sc. secunda by the larger eyes and a more developed conjunctival appendage of the penis. Schiodtella formosana was originally described as lacking tarsi from all legs, whereas all subsequent descriptions mention their presence in all legs. Consequently, the definition of Schiodtella is revised, because the affinity of many significant characteristics between Sc. formosana and other congeners is recognized. The availability of characteristics for a generic definition is discussed.